The value of a in terms of b is given as [tex]a = 8b^3[/tex]
Given the equation solved by Leo expressed as [tex]b=\frac{1}{2}\sqrt[3]{a-1}[/tex]
We are to solve the equation for the variable "a"
Given;
[tex]b=\frac{1}{2}\sqrt[3]{a-1}[/tex]
Cross multiply
[tex]2b=\sqrt[3]{a-1}[/tex]
Cube both sides of the equation:
[tex](2b)^3=(\sqrt[3]{a-1})^3 \\8b^3=a-1[/tex]
Add 1 to both sides of the equation:
[tex]8b^3+1=a-1+1\\8b^3=a\\Swap\\a=8b^3[/tex]
Hence the value of a in terms of b is given as [tex]a = 8b^3[/tex]
Learn more on subject of formula here: https://brainly.com/question/657646